2004
DOI: 10.1002/ajh.20087
|View full text |Cite
|
Sign up to set email alerts
|

Factor V‐Leiden, prothrombin G20210A, and MTHFR C677T mutations among patients with sickle cell disease in Eastern Saudi Arabia

Abstract: The prevalence of factor V Leiden, prothrombin G20210A, and MTHFR C677T mutations were investigated among 87 Saudi sickle cell disease (SCD) patients (38 males and 49 females) and 105 healthy controls (65 males and 40 females). The prevalences of factor V Leiden (P = 0.174) and PRT G20210A (P = 0.397) were not different between patients and controls, thereby giving no support to an association of either single-point mutation with SCD. However, an increased prevalence of the MTHFR 677 T/T genotype was seen amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
3
17
0
2
Order By: Relevance
“…In two separate studies on sickle/b 0 thalassemia and SCD patients from Lebanon and Eastern Saudi Arabia [6,8] a higher but not significant frequency of prothrombin G20210A was detected in these patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In two separate studies on sickle/b 0 thalassemia and SCD patients from Lebanon and Eastern Saudi Arabia [6,8] a higher but not significant frequency of prothrombin G20210A was detected in these patients.…”
Section: Discussionmentioning
confidence: 93%
“…Andrade et al [7] studied the prevalence of the factor V Leiden mutation, 677 C fi T in the methylenetetrahydrofolate reductase (MTHFR), and prothrombin gene variant in SCD patients from Brazil and reported no significant difference between SCD patients and the control Black population related to the prevalence of the studied thrombophilic mutations. Fawaz et al [8] have compared the prevalence of factor V Leiden mutation and prothrombin gene variant in SCD patients from Eastern Saudi Arabia with controls. Their study revealed that there is no association between these single-point mutations with SCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, methylene-tetrahydrofolate reductase deficiency, which is not infrequent in subjects with SCD, [165][166][167][168] would influence host folate status and homocysteine metabolism with possible effects on sickle cell vasculopathy. Similarly, glucose-6-phosphate dehydrogenase deficiency could affect severity of haemolysis in sickle cell anaemia, although some studies of this genotype have shown little additive effect.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Este polimorfismo é mais comum em indivíduos caucasianos saudáveis apresentando uma prevalência de cerca de 2%, sendo extremamente raro em indivíduos com descendência africana (0,67%) e asiática (0,0%) (Rosendaal et al, 1998;Fawaz et al, 2004;Pandey et al, 2012). Entretanto, a prevalência em indivíduos que tiveram evento trombótico aumenta, chegando a 6,2% (Mueller et al, 2005).…”
Section: Polimorfismo No Gene Da Protrombina (F2 20210g>a)unclassified